The City and the super-organism a history of naturalism in urban planning - Amati, Marco 1975- (Springer Singapore Pte. Limited, 2021)
IIntroduction -- Between Naivety and Daily Use -- Why Use Naturalism in Strategic Planning? -- What Is Naturalism? -- Why Discuss Naturalism in Planning Now? -- The Urban Age and the Anthropocene -- The Biological Century -- What This Book Is About -- Tracing Naturalism Through Time -- How This Book Will Unfold -- A City for 'Natural Man' -- Introduction -- The Pathological City -- The City of Melioration -- The Physionomy of the City -- Guaranteeing a City's Survival -- Conclusion -- From an Exterior to an Interior Urban Gaze -- Introduction -- Medical Topographies -- A Medical Topography of Paris -- Interiorising the Transmission of Disease in the City -- Conclusion -- The Vital City -- Introduction -- Mechanism Versus Vitalism -- Bergson's Concept of Vitalism and Evolution -- Vital Energy or Élan Vital -- Evolution of Beings and Societies -- Applying a Mixture of Mechanism and Vitalism with Bergsonian Evolution to Describe Paris -- Conclusion -- Evolving the City -- Introduction -- Geddes' Pragmatism in Relation to Scientific Theories of the City -- Geddes' Concept of Synthesis and Cooperation Through Evolution -- Applying Geddes' Synthetic and Cooperative Approach to Cities -- A Japanese Perspective on City Life -- Geddes' Direct Influence -- Conclusion -- Urban Social Hygiene -- Introduction -- Treating the City to Treat the Nation -- Early Awareness of the Eugenic Potential of Cities -- Eugenics in the Garden -- The Chicago School and Urban Organisms -- Conclusion: Naturalism to Shape Reproduction in Cities and Cement New Disciplines -- The City of Organic Regularity -- Introduction -- Biology as a Source of First Principles -- Biology as a Series of Machines -- Cities and Their Biology Contributing to a Stronger State.